Public Speaking in EFL Settings: The Issue of Overcoming Fears - PATRICIA KIM JIMÉNEZ NIÑO (Universidad Pedagógica y Tecnológica de Colombia, 2008)
Ibisarticle aims atsharing several facts dealing witb tbe art01public speaking. Itisaddressed toundergraduae students, particularly, totbose learners who are acquiring a loreign Iangnage and have experienced speaklng Iimitations. Through the paper, tbeywill find aseries 01 practica! recommendations suggesting how tohandle some pS}l:hologica! faetors such asfears and negative emotions when talking toanaudience.llkewise, readers will be aware 01the necessaryknowledge public taIk involves inorder toachieve asuccessful oral performance. Ibis information might be helpful toimprove not only students' social skills and spoken communication in presentations and lectures, butalso it can become useful inloreign Iangnage classrooms during the socialization 01projects, oral reports, orjustwhen interacting intbe different class discussions. The recommendations are based onsorne autbors' discussions and onpersonal rellections about the issue. 1consider Ibis dala asavaluable contribution for many people who face up Ibis difficulty and want tosucceed inIbis freid.